DIAGNOSIS AND RX-SURGICAL TREATMENT OF THE LIVER HEMANGIOMAS IN CHILDREN - E. I. Petrov; I. V. Kirgizov; Yu. A. Polyaev; R. V. Garbuzov; E. N. Tsygina (Педиатрическая фармакология)
With the introduction into medical practice of highly informative noninvasive diagnostic techniques a refuse from the method of angiographic study appeared, which, according to many authors, was not completely justified. Of all the known today diagnostic techniques, angiography more precisely reveals the pathognomonic signs of the focus formations in the liver, especially hemangiomas, and allows to make a smooth transition from the stage of diagnosis to the treatment — i.e. endovascular occlusion of the hepatic artery [9]. The paper presents the methods of diagnosis, the results of examination and treatment of 58 children with hemangiomas of the liver in the preschool age.